Coherent internal conversion from high lying electronic states to S1 in boron-dipyrromethene derivatives. Issue 44 (3rd November 2021) - Lee, Changmin; Seo, Kiho; Kim, Munnyon; Joo, Taiha
Abstract : Coherent internal conversion between higher electronic excited states is observed directly by excitation of molecules to S n ( n  ≥ 2) state and detection of fluorescence from S1  state by wave-packet-resolved time-resolved fluorescence. Abstract : Internal conversion is the first step after photoexcitation to high lying electronic states, and plays a central role in many photoinduced processes. In this report, we demonstrate a truly ultrafast internal conversion (IC) in large molecules by time-resolved fluorescence (TF). Following photoexcitation to the S n ( n ≥ 2) state, TF of the S1 state was recorded for two boron-dipyrromethene (BODIPY) derivatives in solution. IC to S1 takes place nearly instantaneously within 20 fs for both molecules. Abundant nuclear wave packet motions in the S1 state are manifest in the TF signals, which demonstrates that the IC in these BODIPY molecules is coherent with respect to most of the vibrational modes. Theoretical calculations assuming impulsive IC to S1 account for the wave packet dynamics accurately.